Strategi Pemasaran Pembuatan Taman Kampung dan Penjualan Tanaman Hias di Donomulyo, Malang - Doni Wirshandono Yogivaria; Mochamad Fariz Irianto (Jurnal Syntax Admiration, 2024)
The creation of village gardens and the sale of ornamental plants have the potential to improve the welfare of the Donomulyo community. However, this potential has not been fully utilized optimally. One of the factors that hinder the utilization of this potential is the lack of an appropriate marketing strategy. The purpose of this study is to analyze the marketing strategy of making village gardens and selling ornamental plants in Donomulyo, Malang. This research uses a qualitative method with a case study approach. Data collection techniques in this study were literature study, interviews and observations. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the strategies that can be done to increase the marketing effectiveness of making village gardens and selling ornamental plants in Donomulyo Village include community empowerment, coordination between stakeholders, and developing market access. Marketing strategies for making village gardens and selling ornamental plants in Donomulyo Village need to be optimized to increase the economic value of village gardens and community welfare.